UJI ADAPTASI GALUR HARAPAN/ VARIETAS PADI GOGO PADA EKOSISTEM DATARAN RENDAH DI KABUPATEN DELI SERDANG - Amrizal Yusuf; Yardha Yardha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Adaptation of upland rice promising lines and varieties at ecosystem in lowland Deli Serdang regency. The trials were conducted at Pasar Miring Experimental Farm during dry season of 2009. Activities conducted during that season two was introduced six promosing line and two varieties (Situ Bagendit and Towuti namely) of expectations as a comparison yielding varieties are planted on dry land. The experimental design using randomized block design with three replications. Plot size was 4 x 5 m and plant spacing 20 x 25 cm. Assessment results indicated that the obtained 4 (four) upland rice strains capable of providing results in over 4 t/ha dry grain milling (GKG). Results obtained by comparison of varieties of Towuti and Situ Bagendit respectively 4.58 and 4.87 t/ha GKG, therefore in this study found that 3 strains have the potential of approaching potential outcomes is owned by a variety of the strains comparison SEB. 8FA-281-2, SEB.BSL-4-2, and strain CIRAD 141. While the potential outcome under 4 t/ha are owned by strain of SEB. 8FA-67-5, strains SEB.8FA-300-2, and strain SEB. 8FA-37-2. Strains that have a short harvesting age (under 100 days) obtained in strain SEB. 8FA-281-2 and strains of SEB. 8FA-300-2 while the age crop varieties that are owned by comparison Towuti and Situ Bagendit are 106 and 109 days.